Direito ao dever de cuidar: política de atenção às servidoras do magistério no município de Itumbiara, Goiás, no período de 2015 a 2020 - Marques, Rogério da Silva (2023)
This research, in terms of its objective, explains and presents elements that promote both understanding and reflection on how the right established by law, which guarantees leave to accompany a sick family member and/or with a disability, is implemented specifically in the municipality of Itumbiara, Goiás, from 2015 to 2020. The research has a bibliographic and qualitative character, focused on the field of education, with exploratory documentary field characteristics. The collected data were analyzed and classified according to gender, period of absence, family member demanding absence, self-declared race/ethnicity, whether they have a disabled family member, and whether they perform other professional activities. In this context, reflections arise on the legal duty of care in relation to the labor right to absent oneself to fulfill one's legal responsibility, such as: the care and its political and social contexts in which it occurs; the type of relationship between the caregiver and the care recipient; the domain in which it occurs; the interface between the formal and informal sphere of care; socio-family division/planning of the subjects who must provide care, as well as the impacts of care on the caregiver. Among the results, the necessary guarantee of labor rights to the entire working class stands out, as well as social reflection on care and the overload of women in this process, and the expansion of debates on care and the responsibility of the State as special protection for the family and people with illness and/or disabilities.